(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2019)
The present work studies a concrete case of notation in Alarcos’s book Fonología Española (1950–1965) — the example of <ae>. The study of this glyph allows us to present a model of analysis of systems of notation used in phonological works. This model is based on the relationship between two dimensions – the dimension of texts and the dimension of scientific notation – which is established through the use of two operations: transcription and transliteration. In addition to reflecting on the importance of the study of notation, the final objective of this work is to propose that the scientific texts themselves (on phonology in this case) become an object of study by themselves. Key words: representation theory, notation, transliteration, transcription, glyphs, characters, symbols.